2017
DOI: 10.1016/j.chempr.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Site-Divergent Delivery of Terminal Propargyls to Carbohydrates by Synergistic Catalysis

Abstract: The direct, selective modification of carbohydrates represents a significant challenge in chemistry. Here, we show that synergistic catalysis, a strategy that combines the catalytic effects of two distinct catalysts, could be a powerful tool for addressing the site-selectivity issue during the modification of monosaccharides. By exploiting a borinic acid and a copper catalyst simultaneously, this method enables delivery of valuable terminal propargyl groups to various monosaccharides and natural products in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(37 citation statements)
references
References 67 publications
1
36
0
Order By: Relevance
“…98 A similar report of copper and borinic acid-catalyzed propargylic etherication reactions was also independently carried out by the group of Niu in 2017. 117,118 But the substrate scope is limited and has been limited to diols and polyols, which may coordinate the boron center in a bidentate fashion.…”
Section: Copper Derived Catalystsmentioning
confidence: 99%
“…98 A similar report of copper and borinic acid-catalyzed propargylic etherication reactions was also independently carried out by the group of Niu in 2017. 117,118 But the substrate scope is limited and has been limited to diols and polyols, which may coordinate the boron center in a bidentate fashion.…”
Section: Copper Derived Catalystsmentioning
confidence: 99%
“…In this realm, various methods 21,22 have been established to selectively modify the intrinsically most reactive hydroxyl groups within a substrate (substrate control). Recently, systems that can override the intrinsic reactivity preferences and accomplish catalyst-controlled, site-switchable modification of complex polyols have emerged [23][24][25][26][27][28][29][30][31][32][33][34][35] . As eminent examples, in a series of landmark studies, the Miller group [23][24][25][26] , has identified several oligopeptide-based catalysts that enabled site-switchable modification of complex antibiotics, such as vancomycin, teicoplanin, and erythromycin.…”
mentioning
confidence: 99%
“…[12,13] However,t ot he best of our knowledge,a general method, which uses organoborons for the regioselec-tive functionalization of unprotectedc arbohydrates has not been reported. [14][15][16] This is because the organoboronc atalyst binds to both cis-1,2-diol and 1,3-diolm oieties (Scheme 1e). [12,14] Herein, we describe the chiral benzazaborole-catalyzed regioselective sulfonylation of unprotected carbohydrates.…”
mentioning
confidence: 99%
“…[14][15][16] This is because the organoboronc atalyst binds to both cis-1,2-diol and 1,3-diolm oieties (Scheme 1e). [12,14] Herein, we describe the chiral benzazaborole-catalyzed regioselective sulfonylation of unprotected carbohydrates. [17] Sulfonylated carbohydrates are used as electrophilesi nt he synthesis of biologically interesting pseudosugars and buildingb locks.…”
mentioning
confidence: 99%
See 1 more Smart Citation